A Systematic Review on Comparative Analysis, Toxicology, and Pharmacology of Medicinal Plants Against Haemonchus contortus - Ali, Rehman; Rooman, Muhammad; Mussarat, Sakina; Norin, Sadia; Ali, Shandana; Adnan, Muhammad; Khan, Shahid Niaz (Frontiers in Pharmacology, 2021)
Background:Haemonchus contortus is an important pathogenic nematode parasite and major economic constraint of small ruminants in tropics and subtropics regions. This review is an attempt to systematically address the; (a) efficacy of different plants against H. contortus by in vitro and in vivo proof; (b) toxicology, mechanism of action, and active phyto-compounds involve in anti-haemonchiasis activity; (c) and comparative analysis of plant species evaluated both in vitro and in vivo. Methods: Online databases (Google Scholar, PubMed, Scopus, and ScienceDirect) were searched and published research articles (1980–2020) were gathered and reviewed. Results: A total of 187 plant species were reported belonging to 59 families and 145 genera with Asteraceae and Fabaceae being frequently used. Out of the total plant species, 171 species were found to be evaluated in vitro and only 40 species in vivo. Twenty-four species were commonly evaluated for in vitro and in vivo anti-haemonchiasis activity. Among the reported assays, egg hatching test (EHT) and fecal egg count reduction (FECR) were the most widely used assays in vitro and in vivo, respectively. Moreover, sheep were the frequently used experimental model in vivo. After comparative analysis, Lachesiodendron viridiflorum, Corymbia citriodora, Calotropis procera, and Artemisia herba-alba were found highly effective both in vitro and in vivo. L. viridiflorum inhibited enzymatic activities and metabolic processes of the parasite and was found to be safe without toxic effects. C. citriodora was moderately toxic in vivo, however, the plant extract produced promising nematicidal effects by causing muscular disorganization and changes in the mitochondrial profile. Additionally, C. procera and A. herba-alba despite of their high anti-haemonchiasis activity were found to be highly toxic at the tested concentrations. C. procera caused perforation and tegumental disorganization along with adult worm paralysis. Nineteen compounds were reported, among which anethole and carvone completely inhibited egg hatching in vitro and significantly reduced fecal egg count, decreased male length, and reproductive capacity of female in vivo. Conclusion: This review summarized different medicinal plants owing to nematicidal activities against H. contortus eggs, larvae, and adult worms. Plants like L. viridiflorum, C. citriodora, C. procera, and A. herba-alba, while compounds anethole and carvone having promising nematicidal activities and could be an alternative source for developing novel drugs after further investigation.